The Impact of Customer Relationship Management on Customer Retention at Sentral Mobil Medan: Pengaruh Customer Relationship Management terhadap Retensi Pelanggan di Sentral Mobil Medan - Eddy; Ali Syah Putra; Albert (Jurnal Kolaboratif Sains, 2023)
The role of customers is so vital for organizations and that is why customerrelationship management (CRM) is born based on the recognition of the valuecustomers have. CRM is then known as a managerial approach which is customer customer-oriente d in which information is provided by information systems in order to sustaincollaborative, operational, analytical, and CRM processes leading to customersatisfaction and retention. Sentral Mobil Medan is having problem with the retentionwhich is gettin g low. The objectives of the research are to analyze whther CRM hasimpact on customer retention and determine how strong the impact of CRM oncustomer customer retention in the company. The writer uses Slovin Formula to get thesample size. The sample size is 144 customers. The writer uses the simple randomsampling which each member of the population has an equal and known chance ofbeing selected. The correlation test shows Variable X ( Customer RelationshipManagement) has a significantly strong and positive impact on variable Y (customerretention) at Sentral Mobil Medan. zcount > ztable (9.88 > 1.96), CustomerRelationship Management has impact on customer retention at Sental Mobil Med an.Several recommendations after analysis and results are the staff of Sentral MobilMedan may serve the customers with good manner, give personal attention and how tointeract close what the customers really needs and identify problems and solve theprob lems fast.